Isolated Systolic Hypertension among Diabetes Mellitus Subjects; a national cross-sectional study in Indonesia - Mahalul Azam; Fetty Nur Hidayati; Arulita Ika Fibriana; Udin Bahrudin; Syed Mohamed Aljunid (Jurnal Kesehatan Masyarakat, 2023)
Isolated systolic hypertension (ISH) reflects atherosclerosis. Studies reported hypertension prevalence among diabetes mellitus (DM); however, limited studies provided community prevalence. The present study aimed to explore ISH prevalence among DM in Indonesia. This study obtained data from the 2018 Indonesia Basic Health Survey. The DM category was determined by fasting plasma glucose (PG) level ≥126 mg/dL or 2 hours postprandial and random PG level ≥200 mg/dL or previously diagnosed by a doctor. ISH is categorized if systolic blood pressure is≥140 mmHg and diastolic blood pressure is 90 mmHg. This study also explored the subject’s determinants, i.e., compliance, demography, and lipid profile. A Chi-square and Binary logistic regression were used to determine the association. The study included 3,911 DM individuals and disclosed the prevalence of ISH at 17.5%. ≥65 years old (OR=13.61 95%CI: 3.297-19.365) and 45-64 years old OR=4.59 95%CI: 3.297-6.383)), high HDL-cholesterol (OR=0.77; 95%CI: 0.626-0.936), and longer DM duration (OR=2.89; 95%CI: 2.405-3.474), all together were related to the ISH. Subjects with the oldest age category, i.e., ≥65 years old, had the highest OR. Older DM individuals with low HDL-C and longer DM duration were related to the ISH, suggesting lipid profile treatments, mainly the HDL-C, is a pivotal effort to delay ISH.